Asymmetric shock deformation at the Spider impact structure, Western Australia. (9th March 2021) - Cox, Morgan A.; Cavosie, Aaron J.; Poelchau, Michael H.; Kenkmann, Thomas; Miljković, Katarina; Bland, Phil A.
Abstract: The distribution of shock deformation effects, as well as the structural expression of an impact structure, can be asymmetric, depending on target rock lithologies (e.g., layered versus homogenous), porosity of target rock, and angle of impact. Here, we present a detailed study of shock‐deformed quartz and zircon in silicified sandstones from the asymmetric Spider impact structure in Australia. We utilize optical microscopy and electron backscatter diffraction (EBSD) techniques in order to determine the spatial distribution of shock‐deformed zircon along a downrange transect across the central uplift of the structure, with the goal of constraining the physical distribution of shock effects created by an oblique impact. A total of 453 zircon grains from 12 samples of shatter cone‐bearing quartzite and breccia within the structure were surveyed for shock deformation by EBSD in situ within thin sections. Nineteen zircon grains contain {112} twins, including one grain with three twin orientations. Quartz grains from five samples along the transect were also surveyed using a universal stage in order to determine orientations of planar deformation features, planar fractures, and feather features, and to provide a baseline for comparison of data from zircon. The distribution of shocked zircon with {112} twins within the samples surveyed appears to be asymmetric relative to the center of the structure, in contrast to quartz, thus providing the first accessory mineral‐based evidence that supports an asymmetric distribution of shock deformation as a function of impact obliquity. Our results are an example where the highest intensity of observed shock deformation does not correspond to the geographic center of the structure, and may serve as a guide for field studies aimed at documenting the distribution of shock effects at other sites interpreted to result from oblique impacts.